Di-2-ethylhexyl phthalate induces heart looping disorders during zebrafish development. (July 2021) - Sun, Yangyong; Yang, Fan; Liu, Yang; Yu, Manli; Wu, Feng; Wang, Guokun
Di-2-ethylhexyl phthalate (DEHP) is a type of plasticizer widely used in industry. It is well-known for its toxic effects to endocrine and reproductive systems and has been detected in amniotic fluid and placenta. In the present study, we explored the effects of DEHP on heart development by using zebrafish as a model organism. DEHP (0.02 pg) was injected into the yolk sac of zebrafish embryos at the one-cell stage. No significant difference was found in embryonic lethality between control and DEHP groups at 1-day postfertilization (dpf), but mortality significantly increased in DEHP groups at 2 and 3 dpf. The average heart rate was significantly reduced in the surviving DEHP-treated zebrafish larvae at 3 and 4 dpf. In addition, massive pericardial edema was found in DEHP-treated zebrafish (12.6 ± 1.5%), which was significantly higher than that of the control group. Serious heart looping disorder was also observed in DEHP-treated larvae, mainly manifested with an elongated atrial-ventricular distance. Moreover, the expression of heart development transcription factors was affected by DEHP injection. Real-time polymerase chain reaction confirmed that five transcription factors ( hand2, tp53, mef2c, esr1, and tbx18 ) were significantly downregulated in the DEHP group at 2 dpf, and three transcription factors ( zic3, tcf21, and gata4 ) were significantly upregulated. Our results emphasize the need for the development of a nontoxic plasticizer to prevent possible deleterious effects on humans and other life-forms.